Support for the promotion of historic-with-technology activities (Research, Society and Development, 2020)
As a result of human construction, mathematics is generated by the needs built to meet certain demands of society. Classroom work represents a challenge for the teacher in that it requires him to conduct it in a meaningful and stimulating way for the student. The approach of combining the History of Mathematics (HM), together Digital Technologies of Information and Communication (TDIC), provides an alternative to work mathematics contemplating its teaching. Like this, these work presents the results of research that aims to promote support for the promotion of historical-activities-with-technology as a resource for the teaching of mathematics. Such activities exist in the direction of the connection between HM and TDIC and consist of activities elaborated based on the use of HM in teaching, above all, with the approach of themes/historical problems that can be investigated with the support of TDIC in the light of the Mathematical Investigation (IM) process. In order to promote the proposed contribution, a qualitative research with an exploratory objective of bibliographic procedure was developed, in which a systematic survey was carried out in academic works of the dissertation type. As a result, the essential elements for the production of such activities were obtained, namely: the pre-textual elements, the basic information, the development of the activity and the evaluation, in addition to elucidating the definition of such activities. Thus, as a conclusion of the study, we arrived at the fact that pointing out the elements that make up the historical-activities-with-technology together with the clarification of what consists of them can serve to encourage the elaboration of more activities in this direction in favor of the teaching of mathematics.